A Semi-Analytical Model of Spiral-Groove Face Seals: Correction and Extension. Issue 6 (1st November 2016) - Xiao, Kaiming; Huang, Weifeng; Gao, Wenbin; Liu, Xiangfeng; Wang, Yuming
ABSTRACT: This article presents a semi-analytical model of spiral-groove face seals. Based on Muijderman's spiral-groove bearing theory for parallel faces, a one-dimensional radial discretization method is proposed to process the radial variations of different parameters of face seals. For each discrete element, the geometric parameters of the faces (e.g., film thickness, groove shape) and the physical parameters of the lubricant (e.g., density, viscosity) can be assigned to reflect the radial nonuniformity of these parameters. Furthermore, a correction of the end effect is introduced to improve the model's precision. Errors in this model under various operating conditions and with different design parameters are analyzed by comparison with the traditional one-dimensional difference model and the two-dimensional numerical model. The calculation results indicate that the proposed model is more accurate than the traditional one-dimensional difference model under various conditions. Furthermore, it is shown that the proposed model could be applied to the analysis and design of face seals with different types of grooves and lubricants as well as different radial nonuniformities in their geometric and physical parameters. These extended applications of the proposed model could provide good approximations to the two-dimensional numerical results. This semi-analytical model has the benefits of an analytical method (e.g., simple preprocessing, high efficiency, and the ability to manage large-scale parameter optimization) and of a numerical method (e.g., the ability to be applied to extended applications of face seals with shallow grooves).